Plant stature heritability in wheat: estimate through the regression coefficient - Carvalho, Fernando I.F. de; Uitdewilligen, Wilhelmus P.M.; Federizzi, Luiz C.; Gomes, Edar P.; Pfeifer, Alcenise B.; Matos, Matias A.O. (Pesquisa Agropecuaria Brasileira, 2014)
The study reported herein was designed to determine the relationship between the plant stature trait performance of F3 or F4 or RC1 F2 derived lines from F2 or F3 or RC1 F1 in several hexaploid wheat crosses, respectively. The heritability results greater than one were computed through the standard unit method by calculating the regression on data coded in terms of standard deviation units. A comparison was made between heritability estimated by these two methods, conventional and standard units. Heritability estimates provides useful guidelines of answering many questions which arise in a plant breeding program.